2003
DOI: 10.1046/j.1492-7535.2003.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Options for Pediatric Hemodialysis

Abstract: Blood coagulation in the extracorporeal hemodialysis circuit is one of the manifestations of bio-incompatibility that is related to the activation of monocytes, platelets, and the coagulation cascades. Compared to adults, in pediatric patients, the surface area of the extracorporeal circuit is increased relative to blood volume. This is due to the patient's smaller blood volume and the combination of the higher relative surface area of the dialyzer, smaller lumen lines, and small-bore vascular catheters, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…A receiver-operator characteristic graph calculated from our data showed that a post-filter iCa <0.30 mmol/l is needed to reliably achieve a post-filter ACT >120 s. In accordance with the published results of Calatzis et al [13], we found a hyperbolic relationship between post-filter coagulation time and postfilter iCa, with a high correlation between both parameters. We therefore recommend keeping the post-filter iCa <0.30 mmol/l for adequate anticoagulation in regional citrate anticoagulation, as supported by the recommendations of Ward and Davenport [11,20]. In our experience the post-filter iCa is a suitable parameter for monitoring anticoagulation of the extracorporeal circuit in RCA in iHD.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A receiver-operator characteristic graph calculated from our data showed that a post-filter iCa <0.30 mmol/l is needed to reliably achieve a post-filter ACT >120 s. In accordance with the published results of Calatzis et al [13], we found a hyperbolic relationship between post-filter coagulation time and postfilter iCa, with a high correlation between both parameters. We therefore recommend keeping the post-filter iCa <0.30 mmol/l for adequate anticoagulation in regional citrate anticoagulation, as supported by the recommendations of Ward and Davenport [11,20]. In our experience the post-filter iCa is a suitable parameter for monitoring anticoagulation of the extracorporeal circuit in RCA in iHD.…”
Section: Discussionmentioning
confidence: 57%
“…The ACT has also been advocated as a routine preoperative screening test for detecting coagulation disorders [18,19]. As a whole blood coagulation test, the ACT is affected by different anticoagulants and therefore can be used for monitoring the effects of unfractionated heparin, nafamostat, aprotinin, citrate, and hirudin [20]. It is also affected by certain congenital disorders of coagulation, warfarin, and liver failure [18,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations